Somatic treasures : Function and Reception of Effigies on Holy Tombs in Fourteenth Century Venice - Munk, Ana (Array, 2011)
The article explores the function of effigies in the design of holy shrines in late medieval Venice. Even though representations of deceased laymen were a common feature in sepulchral art, precedent-making holy shrine, Nicola Pisano’s tomb for Saint Dominic from 1267, did not include an effigy. Even much later elaborate shrines, such as the tomb of Saint Peter Martyr (1335-9) by Giovanni di Balduccio, refer to the deceased through a mourning scene, although that scene takes a prominent frontal place in the narrative relief. In Venice, however, we find a concentration of effigial tombs such as the one that Venetians acquired for relics of Saint Simeon by Marco Romano (1318). An earlier or coeval shrine for the same Old Testament prophet in Zadar is equally an effigial shrine, although the body is sculpted as a high relief rather than a three-dimensional sculpture. Equally as well, Filipo de’Santi‘s Venetian work for the deceased Blessed Odorico da Pordenone (1332) is an effigial tomb that demonstrates the purpose of such tomb design: to create a simulacrum of the precious tomb content of miracle working relics. The main premise of this discussion is derived from pilgrims’ accounts that testify to the fact that relics, fragmentary or full-body, were the main attraction at Venetian churches. Starting with the end result — viewers’ reaction to holy sites — this research attempted to isolate the representations of the dead body and elucidate some artistic choices that artists made in order to enhance the viewer’s experience.